ANALISA ALIGNMENT SHAFT TURBIN GAS - Ramadani, Dwi; Suryadi, Dedi; Bismantolo, Putra (UNIB Press, 2024)
In the gas turbine system there is a section that functions as a place for combustion between a mixture of air and gas called the combustion section. The components of the alignment of the shaft need to be maintained regularly so that the resulting combustion is good. In the process of the turbine producing electrical energy there are many obstacles that occur which result in a reduction in the productivity of the turbine work, one of the causes is misalignment of the shaft. Misalignment on the shaft can be overcome by carrying out an alignment process which aims to make the shaft return to its initial position so that it is parallel to the other shaft. The alignment process is carried out to get the axial and radial values on the shaft which is then carried out by the adjusting process. The adjusting process is carried out so that the position of the shaft that is out of tolerance returns to the tolerance position and the work of the turbine can return to normal.